Development of novel agonists for the orphan nuclear receptor, Nurr1 : a therapeutic strategy for Parkinson’s disease - Toh, Hui Ting (Nanyang Technological University, 2019)
Parkinson’s Disease (PD) is the second most prevalent neurodegenerative disease among the elderly. It is characterized pathologically by the demise of dopaminergic (DA) neurons in the substantia nigra region of the midbrain resulting in the loss of motor function. The orphan nuclear receptor, Nurr1, has presented itself as an attractive drug target for PD due to its significant involvement in the development and maintenance of mid-brain DA neurons. Till date, Nurr1 remains an orphan nuclear receptor due to the lack of identified endogenous ligands. Preliminary high-throughput drug screening efforts via X-ray crystallization by our lab have revealed the binding of a specific class of eicosanoids with Nurr1 ligand binding domain (LBD). In this thesis, the binding site of these eicosanoids, and their precursors, was characterized on Nurr1 LBD using nuclear magnetic resonance (NMR) spectroscopy. The ability of these ligands to activate the transcriptional function of Nurr1 was determined using a cell-based luciferase reporter system. Furthermore, their treatments on (a) LRRK2 G2019S transgenic flies and (b) 6-hydroxydopamine (6-OHDA) neurotoxin-induced mice models demonstrated improved locomotor function and rescued tyrosine hydroxylase positive (TH+) neuronal loss. The discovery that these eicosanoids interact with Nurr1 LBD and activate its function, lay the groundwork for future development of neuroprotective and disease-modifying therapies for PD that can help slow down further progression of the disease.